Historiografi Kepahlawanan Haji Salahuddin Talabuddin sebagai Pemerkaya Bahan Ajar Sejarah untuk Penguatan Karakter Gen-Z Maluku Utara - Ode Bau, Suharlin (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2025)
This study highlights the urgency of local hero historiography as a means to strengthen collective identity and foster the character of younger generations, particularly Gen-Z in North Maluku. Haji Salahuddin Talabuddin, officially recognized as a National Hero in 2022, is positioned as a representation of local resistance that is highly relevant to be integrated into history education. The purpose of this research is to reconstruct the heroic narrative of Salahuddin Talabuddin and to explore its potential integration into history learning materials as a medium for Gen-Z character development. This research employs a library research method with a qualitative approach by examining primary and secondary sources, including official archives, academic publications, and credible online news. The findings reveal that the historiography of Salahuddin Talabuddin reflects the fusion of religiosity and politics in anti-colonial resistance while conveying values of courage, integrity, and solidarity that align with Gen-Z’s character education needs. The integration of his heroic narrative into learning materials is proven to enhance critical literacy, historical empathy, and national pride. Supported by digital media and contextual approaches, local historiography transforms from a mere historical record into a pedagogical instrument that adapts to contemporary challenges. This study enriches the historiographical discourse of Indonesian education by integrating local values of North Maluku into the character curriculum for Generation Z.